ANALISIS TINDAK TUTUR DALAM NOVEL MY LECTURER MY HUSBAND KARYA GITLICIOUS (KAJIAN PRAGMATIK) - Karolina Dawus; Ni Luh Sukanadi; Ida Ayu Made Wedasuwari (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research is a descriptive study that aims to describe the types of directive and expressive speech acts in the novel "My Lecturer My Husband" by Gitlicious and describe the function of speech acts in the novel "My Lecturer My Husband" by Gitlicious. This study has two problem formulations, namely (1) What are the types of directive and expressive speech acts in the novel "My Lecturer My Husband" by Gitlicious and (2) What are the functions of directive and expressive speech acts in the novel "My Lecturer My Husband" by Gitlicious. The theory that underlies this research is (1) the notion of novel, (2) the nature of pragmatics, (3) the notion of pragmatics, (4) the notion of speech acts, (5) aspects of speech situations, (6) types of speech acts. This study uses instruments, namely tools that are selected and used by researchers in data collection activities so that these activities become systematic. In qualitative research, the research instrument or tool is the researcher himself. Data collection is done by recording method, library method and documentation method. The data obtained were analyzed descriptively qualitatively. The steps in analyzing the data are (1) reducing the data, (2) presenting the data, (3) verifying the data, (4) and concluding the data. The results of this study indicate that 36 indicators of directive speech acts and 14 indicators of expressive speech acts were found. In this study, the research found each type of directive and expressive speech acts in the novel My Lecture My Husband by Gitlicious. There are 4 directive speech acts, asking for 2, asking for 10, asking for 3, urging 1, suggesting 5, ordering 7 and begging 4. And expressive speech acts 3, saying thank you is 1, criticizing is there 2, congratulating 2, complaining 2 and blaming 3. While in terms of function, the researcher found that there were 35 indicators of directive speech act functions and 12 indicators of expressive speech act functions. From each function of the speech act in the novel My Lecturer My Husband by Gitlicious, the researcher found the directive speech act function of forcing, asking, ordering, inviting, urging, suggesting, ordering and pleading. While the function of expressive speech acts, the researcher only found the functions of praising, thanking, criticizing, congratulating, complaining and blaming